Harnessing impact investing: a transformative strategy for CSR in Namibia - Kamenjono, Nguvitjita (Graduate School of Business (GSB), 2025)
Impact investing is a powerful tool for amplifying positive social and environmental impact that Namibian companies can use as a transformative avenue to fulfil their CSR commitments. This innovative strategy empowers companies to drive positive social impact, strengthen brand equity, and foster stakeholder engagement, all while addressing critical socio-economic challenges such as inequality, unemployment, and poverty. However, the intersection between CSR and impact investments in Namibia remains unexplored. This study utilised an inductive qualitative research approach to understand the existing CSR practice with a particular focus on entrepreneurship support in Namibia. Thereafter, understanding the extent to which the participants engage in impact investing strategies for CSR spending while examining the challenges and barriers to the adoption of these strategies. Semi-structured in-depth interviews were conducted with 11 CSR managers or equivalents across 11 different organisations in Namibia, revealing several key findings. The findings revealed national priorities as a prime driving factor for entrepreneurship development and support in CSR practice, being the third most CSR-supported area. The findings also exposed a limited understanding of impact investing in corporate Namibia despite the keen interest strongly displayed by most research participants. Additionally, the most frequently cited barriers to engaging in an impact investing strategy included the lack of bona fide and proper entrepreneurs, collaboration, and appropriate expertise within the organisation. This study contributes to impact investing and CSR in practice and theory by providing a theoretical praxis model that envisages the relationship between these constructs in practice in a meaningful way. The attempt at a praxis model outlines practical steps to effectively mobilise CSR funds towards national priorities while bridging the funding gap in the impact investing market in Namibia.